Highly stable and stretchable graphene–polymer processed silver nanowires hybrid electrodes for flexible displays. Issue 7 (7th January 2015) - Zhang, Qi; Di, Yanfei; Huard, Chad M.; Guo, L. Jay; Wei, Jie; Guo, Jinbao
Abstract : Highly stable and flexible graphene–polymer processed silver nanowires hybrid transparent electrodes and their application for flexible liquid crystal display were demonstrated. Abstract : A new type of highly stable, transparent and flexible hybrid electrode has been developed by integrating the encapsulation of a silver nanowires (AgNWs) network by polyvinyl alcohol (PVA) with a single-layer graphene on a flexible substrate. Compared with commercial indium tin oxide (ITO) film and pristine AgNWs–graphene hybrid film, this hybrid electrode formulation was found to exhibit excellent optical and electrical properties (84.0% at 550 nm R S = 14.1 Ω □ −1 ). Moreover, the PVA encapsulated-AgNWs–graphene hybrid electrode on a flexible substrate shows superior mechanical flexibility, reliability and long-term stability due to the multi-functional effects of PVA as the encapsulation layer. Finally, we employ this hybrid electrode to construct a flexible cholesteric liquid crystals (Ch-LCs) device, where the PVA layer in hybrid formation could be used as the orientation layer. This Ch-LCs device exhibits an impressive electrical–optical performance, demonstrating its potential as a transparent and stretchable electrode platform for flexible optoelectronics.